Multilingual dictionary of fish and fish products = (Fishing News Books, 1990)
A reference work to facilitate international trade in fish and fish products by making available a comprehensive source of specialized information and general knowledge on fish, other marine life and fish products in commercial use. The main text comprises some 1200 entries giving scientific names and in English and French the local names and usage with an indication of methods of processing and marketing. The equivalent of these items is given in 14 other languages whenever possible. The second part consists of separate indices for scientific names, Danish, Dutch (Flemish), English, Finnish, French, German, Icelandic, Italian, Japanese, Norwegian, Portuguese, Serbo-Croat, Spanish, Swedish and Turkish